Pengaruh Arus Kas Bebas (Free Cash Flow) Dan Ukuran Dewan Komisaris Independen Terhadap Kebijakan Pembayaran Dividen Pada Perusahaan Manufaktur Yang Terdaftar Di Bei Periode 2022-2024 - Sarah Siti Zahroh; Susan Kurniawati; Yane Devi Anna (Hikamatzu | Journal of Multidisciplinary, 2026)
This study aims to analyze the effect of free cash flow and the size of the independent board of commissioners on dividend policy in manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the 2022–2024 period. This study used a sample of 25 manufacturing companies selected using a purposive sampling method over three years of observation, resulting in 75 observations. Using multiple linear regression, the analysis showed that, partially, free cash flow had no effect on dividend policy because companies prioritized liquidity for post-pandemic recovery. The size of the independent board of commissioners was also found to have no effect, indicating that the agreement remains limited to administrative regulations. However, both variables simultaneously had a significant effect on dividend policy. These results suggest that companies maintain consistency in profit distribution, investors should pay more attention to capital expenditure plans than board composition, and future researchers should add other variables to broaden the scope of the analysis